2018
DOI: 10.21815/jde.018.007
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Perceptions of Risk Factors for Musculoskeletal Disorders: Adapting the Job Factors Questionnaire for Dentistry

Abstract: The aims of this study were to adapt the Job Factors Questionnaire to the field of dentistry, evaluate its psychometric properties, evaluate dental students' perceptions of work/study risk factors for musculoskeletal disorders, and determine the influence of gender and academic level on those perceptions. All 580 students enrolled in two Brazilian dental schools in 2015 were invited to participate in the study. A three-factor structure (Repetitiveness, Work Posture, and External Factors) was tested through con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…4,12,13 Strategies should therefore be implemented in their academic programmes in an attempt to reduce this risk. [14][15][16][17] A strategy adopted years ago by the School of Dentistry of UNESP Araraquara is the requirement of a practical course on ergonomics in dentistry. 4,7 Despite these efforts, students were found to still have difficulty adopting the ergonomic posture taught in the ergonomics in dentistry course.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13 Strategies should therefore be implemented in their academic programmes in an attempt to reduce this risk. [14][15][16][17] A strategy adopted years ago by the School of Dentistry of UNESP Araraquara is the requirement of a practical course on ergonomics in dentistry. 4,7 Despite these efforts, students were found to still have difficulty adopting the ergonomic posture taught in the ergonomics in dentistry course.…”
Section: Discussionmentioning
confidence: 99%
“…Presoto et al built further upon Garcia's 20 work at the same university assessing dental students' knowledge of work related risk factors for developing MSDs. 21 The author recognized the importance of awareness of risk factors in influencing the individual to preemptively practice ergonomics. The author explains that, "such assessments may provide insight into the adequacy of the training process to protect dentists' occupational health."…”
Section: Studies On Dental Student Knowledge Of Ergonomicsmentioning
confidence: 99%
“…The author explains that, "such assessments may provide insight into the adequacy of the training process to protect dentists' occupational health." 21 Presoto found that women had a higher academic level of awareness of risk factors and suggested this may be due to a higher incidence of pain among women. The author referred to a study completed by Hofftman et al…”
Section: Studies On Dental Student Knowledge Of Ergonomicsmentioning
confidence: 99%
“…Musculoskeletal disorders are common morbidities in dental practice and are characterized by persistent pain and/or discomfort in the musculoskeletal system, including joints, ligaments, tendons, nerves, and structures that support the limbs; these disorders may present as inflammatory or degenerative conditions that occur either alone or by cumulative trauma, causing painful symptomatology in different parts of the body [1][2][3][4][5] . In addition to pain, they include complaints such as tingling, numbness, weight, and early fatigue; thus, these diseases contribute to the inability of the professional from his job, and even their withdrawal from the position 6 .…”
Section: Introductionmentioning
confidence: 99%